Impact of Exercise Training at Maximal Fat Oxidation Intensity on Metabolic and Epigenetic Parameters in Patients with Overweight and Obesity: Study Protocol of a Randomized Controlled Trial - Marco Antonio Hernández-Lepe; David Alfredo Hernández-Ontiveros; Isaac Armando Chávez-Guevara; Arnulfo Ramos-Jiménez; Rosa Patricia Hernández-Torres; Reymond Josué López-Fregoso; Omar Ramos-Lopez; Francisco José Amaro-Gahete; Raquel Muñiz-Salazar; Francisco Javier Olivas-Aguirre (Journal of Functional Morphology and Kinesiology)
Background: Exercise is an essential pillar for human health, as it contributes to physical, mental, and emotional well-being. Well-recognized international organizations, such as the World Health Organization, advocate for integrating exercise into healthy lifestyles, recognizing its importance in disease prevention and improving quality of life. However, despite the consensus on its value, there is no universal agreement on specific prescriptions for vulnerable groups, highlighting the need for personalized approaches that consider the unique characteristics and needs of everyone. Emerging studies have demonstrated that exercise training performed at the intensity that elicits maximal fat oxidation improves insulin sensitivity, cardiorespiratory fitness, and body composition in patients with obesity, making it a highly effective strategy for long-term weight management and metabolic health in this specific population. Methods: The present study protocol settles the basis for a 16-week randomized clinical trial based on exercise prescription at the maximal fat oxidation rate combined with resistance training in young individuals with overweight and obesity. Expected Results: This study will elucidate how FatMax, with or without resistance exercises, can enhance metabolic flexibility, increase fat oxidation, and improve body composition, evaluating changes in biochemical parameters (cholesterol, glucose, triglycerides, and inflammatory markers), metabolic biomarkers (determination of fat and carbohydrate utilization rates during rest and exercise), and epigenetic indicators (focusing on microRNAs associated with adipogenesis, inflammation, and fat metabolism). ClinicalTrials.gov identification number: NCT06553482 (FatMax Training on Metabolic and Epigenetic Parameters).